2005
DOI: 10.1051/0004-6361:20042248
|View full text |Cite
|
Sign up to set email alerts
|

TeV gamma-ray observations of SS-433 and a survey of the surrounding field with the HEGRA IACT-System

Abstract: Abstract. We present results of a search for TeV γ-ray emission from the microquasar SS-433 and the surrounding region covering a ∼8 • × 8 • field of view. Analysis of data taken with the HEGRA stereoscopic system of imaging atmosphericČerenkov imaging telescopes reveals no evidence of steady or variable emission from any position. Observation times of over 100 h have been achieved in central parts of the field of view. We set 99% confidence level upper limits to a number of a-priorichosen objects of interest,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
(28 reference statements)
0
26
0
Order By: Relevance
“…It is intriguing that a Whipple observation of this region showed an excess of gamma-ray-like events over the entire field of view, which was deemed unlikely to be due to a bright, extended source [40]. A number of interesting objects are located near this area, perhaps the foremost being the microquasar SS 433 and its SNR, W50, from which no TeV emission was discovered by HEGRA [41]. Other systems worth noting are SNR G40.5-0.5 [42], HMXB 4U 1909+07 [43], candidate SNR 041.3-01.3 [44], and a prominent molecular cloud complex [45].…”
Section: What Else Is Out There?mentioning
confidence: 98%
“…It is intriguing that a Whipple observation of this region showed an excess of gamma-ray-like events over the entire field of view, which was deemed unlikely to be due to a bright, extended source [40]. A number of interesting objects are located near this area, perhaps the foremost being the microquasar SS 433 and its SNR, W50, from which no TeV emission was discovered by HEGRA [41]. Other systems worth noting are SNR G40.5-0.5 [42], HMXB 4U 1909+07 [43], candidate SNR 041.3-01.3 [44], and a prominent molecular cloud complex [45].…”
Section: What Else Is Out There?mentioning
confidence: 98%
“…The application of this model to SS 433/W50 yielded fluxes at the level of ∼10 −13 erg cm −2 s −1 for E > 250 GeV for an assumed distance to the system of 5.5 kpc (Bordas et al 2010), which are roughly at the level of the upper limits reported here. However, as noted in Aharonian & Atoyan (1998) (see also discussion in Petre 1999 andAharonian et al 2005), electrons accelerated at the interaction region shock interface could lose most of their energy mainly through synchrotron emission for ambient magnetic fields at or above ∼ 10 µG, preventing an effective channelling through IC scattering that is relevant for the production of gamma rays at high and very high energies. The integral flux upper limits for the interaction regions shown in Table 2, together with the assumption that the same high-energy electron population is responsible for the observed (synchrotron) X-ray emission and the putative gamma-ray fluxes, can be used to constrain the magnetic fields present in the shocked SS 433 jets/ISM interaction regions.…”
Section: Discussionmentioning
confidence: 96%
“…analyses were optimized assuming a source radius (θ-cut) of 0.05 • , 0.17 • , 0.25 • , 0.07 • , and 0.07 • for e1, e2, e3, w1, and w2, respectively, derived from the extension of these regions observed at X-ray energies (see e.g. Safi-Harb & Ögelman 1997; Safi-Harb & Petre 1999; Aharonian et al 2005, and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations